Three-Dimensional Carpal Kinematics after Carpal Tunnel Release - Schiller, Jonathan R.; Brooks, Jeffrey J.; Mansuripur, P. Kaveh; Gil, Joseph A.; Akelman, Edward (Journal of Wrist Surgery, 2016)
Background Carpal tunnel release (CTR) has been shown to change carpal arch morphology. However, the effect of CTR on the three-dimensional kinematics of the carpal bones has not been demonstrated.Purpose This study examined whether release of the transverse carpal ligament (TCL) would alter the three-dimensional kinematics of the carpus, specifically the bony attachments of the TCL.Methods The in vitro kinematics of the carpus was studied in five fresh-frozen cadaveric wrists before and after CTR using three-dimensional computed tomography. The specimens were evaluated in three positions: neutral, 60 degrees of flexion, and 60 degrees of extension.Results The data indicate that carpal arch width increases significantly in all positions after CTR as measured between the trapezium and hamate. Second, the trapezium–hamate distance increases in both a translational and rotational component after CTR. Additionally, the pisiform rotates away from the triquetrum after CTR.Conclusions Carpal kinematics is significantly altered with a CTR, especially on the ulnar side of the wrist.Clinical Relevance Although the kinematic changes are small, they may be clinically significant and potentially responsible for pillar pain or postoperative loss of grip strength.
Keywords: carpal arch width; carpal kinematics; carpal bone contours; carpal tunnel release; transverse carpal ligament